Upgrading intrathecal morphine for postoperative pain mitigation in abdominal surgery: an exploratory multiple regression analysis of observational data addressing co-administered spinal magnesium sulfate, en route to both enhanced systemic opioid sparing and opioid avoidance - Williams, Brian A.; Choragudi, Ridhi; Schumacher, Christopher A.; Garbelotti, Kelly E.; Ezaru, Catalin S.; Boudreaux-Kelly, Monique Y.; La Colla, Luca; Ludden, John M. (Frontiers in Anesthesiology, 2025)
BackgroundFor major abdominal surgery, we explored “usual” opioid-avoiding effects of spinal magnesium 25 mg added to intrathecal morphine (250+ µg in women, 300+ µg in men; ITM + Mg+). We evaluated associated benefits of several integrated care “bundles”: 5-drug antiemetic prophylaxis, multiple-day postoperative antiemetic boosters (perphenazine and aprepitant), boosters for non-opioid transitional analgesia, and strategically-avoided usual opioids intraoperatively (fentanyl, hydromorphone, etc.). We also explored antiemetic outcomes, and pruritus, on postoperative days 0–2. We hypothesized these bundles would independently and interactively influence associated outcomes.MethodsWe used a mixed-method framework to demonstrate whether these bundles, integrated with ITM + Mg+, were all associated with one or more milestones en route to improving described outcomes [prevented postoperative nausea/vomiting (PONV), avoided postoperative opioids, etc.]. We did so via retrospective, case-matched quality improvement methodology for a single-hospital population of ITM-receiving Veterans, applying multiple regression to determine (i) PONV prevention success on days 0–1 separately from day 2, (ii) success of avoiding usual opioids (by withholding discretionary fentanyl/hydromorphone intraoperatively en route to avoiding the need for patient-requested hydromorphone/oxycodone postoperatively), and (iii) predictors/signals of itching, including related to the ITM-upgrade to ITM + Mg+.ResultsITM + Mg+, at the described doses, supported by 5-antiemetic prophylaxis and three-drug non-opioid transitional analgesics, was associated with significant opioid-avoiding improvements. Postoperative avoidance of usual opioids was associated with both ITM + Mg+ use and intraoperative and immediate postoperative avoidance of “usual opioids” (fentanyl, hydromorphone, etc.). PONV on days 0–1 (vs. day 2) appears to have differing predictor patterns, warranting both 5-MMAEPPx preoperatively, and future antiemetic upgrade from 2-drug booster prophylaxis (perphenazine/aprepitant) to also include palonosetron every 40 h. ITM historical control major abdominal surgery cases before ITM + Mg+ had a 14% “usual opioid avoidance rate” (35/246), which showed significant associated improvements with ITM + Mg+ use, usual opioid avoidance, and integration with the other described care bundles (34/60, 57%, P < 0.001).ConclusionMultiple “bundles” appear to address both sustained antiemetic success and “usual opioid avoidance.” ITM-related pruritus requires further study regarding prophylaxis and treatment, in order to allow ITM + Mg+ to achieve its full enhanced recovery potential, when trying to avoid postoperative exposure to usual opioids.